2019
DOI: 10.1088/1367-2630/ab4d8f
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous caustics and Veselago focusing in 8-Pmmn borophene p–n junctions with arbitrary junction directions

Abstract: Negative refraction usually demands complex structure engineering while it is very natural for massless Dirac fermions (MDFs) across the p-n junction (PNJ), this leads to Dirac electron optics. The emergent Dirac materials may exhibit hitherto unidentified phenomenon due to their nontrivial band structures in contrast to the isotropic MDFs in graphene. Here, as a specific example, we explore the negative refraction induced caustics and Veselago focusing of tilted MDFs across 8-Pmmn borophene PNJs. To this aim,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…It is important to note that the Landau level spectra (8) depends on the valleys K and K'. The factor (9) indicates whether the orbits are closed when |β ν | < 1 or opened for |β ν | ≥ 1 [11,73,74]. The transition from closed to opened orbits appears for the collapse of Landau levels at the critical value of β ν = ±1, where classically the electrons travel on a straight line.…”
Section: Electron Dynamics In Tilted Anisotropic Dirac Cone Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that the Landau level spectra (8) depends on the valleys K and K'. The factor (9) indicates whether the orbits are closed when |β ν | < 1 or opened for |β ν | ≥ 1 [11,73,74]. The transition from closed to opened orbits appears for the collapse of Landau levels at the critical value of β ν = ±1, where classically the electrons travel on a straight line.…”
Section: Electron Dynamics In Tilted Anisotropic Dirac Cone Materialsmentioning
confidence: 99%
“…Most of the two-dimensional materials discovered so far, such as borophene, strained graphene, Weyl semimetals, and the organic conductor α-(BEDT-TTF) 2 I 3 present anisotropy and tilted Dirac cones in their low energy band structure [1][2][3][4][5][6][7][8][9][10][11][12]. The intrinsic anisotropy of some materials like phosphorene has shown intriguing phenomena such as negative reflection, antisuper-Klein tunneling, and perfect electronic waveguides [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ballistic electron propagation in 2D materials allows the observation of analogies from optics [42,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. For example, it has been shown that an electron beam, which hits the interface of a pn junction, is refracted similar to a light beam at the interface of two different media.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum Fermi velocity of 8-P mmn borophene along the chain direction is nearly 1.5 times that of graphene [9]. Such unique band structure stimulated further study of the electronic properties of 8-P mmn borophene, such as anisotropic plasmons, magnetotransport properties, anomalous Klein tunneling, valley-dependent electron retroreflection, Veselago focusing, Ruderman-Kittel-Kasuya-Yosida exchange interaction, metal-insulator transition, and the photoinduced Hall effect [11][12][13][14][15][16][17][18][19][20]. Most recently, a variety of exotic electronic states, including flat-band phases, superconductivity, magnetism, and the Chern insulators phases, were discovered moiré superlattice systems based on multilayer graphene [21][22][23][24][25].…”
mentioning
confidence: 99%